Short report: Relationships between sensory processing, repetitive behaviors, anxiety, and intolerance of uncertainty in autism spectrum disorder and Williams syndrome. Issue 5 (28th March 2019) - Glod, Magdalena; Riby, Deborah M.; Rodgers, Jacqui
Abstract : Autism spectrum disorder (ASD) and Williams syndrome (WS) share psychopathology relating to sensory processing and repetitive behaviors. The relationships between the sensory features and repetitive behaviors in both disorders, and the mechanisms underlying these relationships are not well understood. The aim of this study was to examine the relationships between sensory processing, repetitive behaviors, anxiety, and intolerance of uncertainty in children with ASD and those with WS to better understand the complexity of psychopathology in these disorders. Parents of 19 children with ASD and 16 children with WS, aged between 4 and 9 years, were asked to complete questionnaires assessing their children's sensory experiences, anxiety symptoms, severity and frequency of repetitive behaviors, and level of intolerance of uncertainty. Serial mediation analysis was performed. Direct significant relationships between sensory features and repetitive behaviors were found only for the ASD group. The relationship between sensory processing difficulties and repetitive behaviors was mediated via intolerance of uncertainty in WS. The findings support the value of considering the complexity of the mechanisms underlying the relationship between sensory processing and repetitive behaviors across neurodevelopmental disorders and the mechanisms underlying these aspects of psychopathology in these groups. Understanding these relationships will shed light on some of the most challenging and intractable characteristics of both conditions and inform suitable interventions to improve quality of life for individuals with either ASD or WS. Autism Research 2019, 12: 759–765 . © 2019 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: In autism spectrum disorder (ASD) and Williams syndrome (WS) difficulties processing the sensory aspects of the environment, repetitive behaviors and high levels of anxiety co‐occur, but the relationships between these features are not well understood. This study found that sensory difficulties were directly associated with repetitive behaviors in children with ASD, but not WS, and in WS this relationship was mediated by intolerance of uncertainty. The findings support the value of considering the complexity of the mechanisms underlying the relationship between sensory processing and repetitive behaviors across neurodevelopmental disorders.